2003
DOI: 10.1067/mtc.2003.77
|View full text |Cite
|
Sign up to set email alerts
|

Continuous retrograde blood cardioplegia is associated with lower hospital mortality after heart valve surgery

Abstract: This study shows that continuous retrograde blood cardioplegia is associated with lower hospital mortality in heart valve operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Retrograde perfusion through the coronary sinus avoids the possibility of aortic insufficiency and is used routinely for cardioplegia delivery during cardiac surgery 9,10 but its use for machine perfusion of donor hearts is rudimentary at best. 11 Furthermore, we previously reported that right ventricular perfusion was reduced in canines when using retrograde perfusion, illustrating a potential limitation of this technique.…”
mentioning
confidence: 99%
“…Retrograde perfusion through the coronary sinus avoids the possibility of aortic insufficiency and is used routinely for cardioplegia delivery during cardiac surgery 9,10 but its use for machine perfusion of donor hearts is rudimentary at best. 11 Furthermore, we previously reported that right ventricular perfusion was reduced in canines when using retrograde perfusion, illustrating a potential limitation of this technique.…”
mentioning
confidence: 99%
“…8,9 In addition to perfusion of capillary beds, RP may also provide partial nutrient flow by perfusion of sinusoids and Thebesian channels. This study examined the use of hypothermic retrograde machine perfusion for a long preservation of donor hearts in a large-animal model of cardiac transplantation.…”
mentioning
confidence: 99%